Integrating Islamic Values on Building Knowledge of the Field Stage at Teaching Procedure Text in EFL Classroom - M.Pd, Lina; Yiyin Isgandi; Achmad Anang Darmawan (STKIP AL HIKMAH SURABAYA, 2025)
Emphasizing Islamic values for ELT teachers in Indonesia are required including in the skill of opening lessons, especially in the institutions of ministry of religions. It was led this his study has aims to describe alternative ways of integrating Islamic values into the opening of procedure text. This qualitative study, which employs a library research method, collected primary and secondary data from various literatures. As results indicate that teachers cannot select effective and efficient methods to integrate Islamic values into opening lessons on procedure text material, tailored to the students' needs, learning objectives, and available time allocation. The alternatives were recommended are: (1) capturing attention: Using personal physical appearance that reflects Islamic values, non-physical expressions, utilizing teaching aids with Islamic law. (2) providing learning guidelines: Explaining the learning outcomes, objectives, steps of activities, setting boundaries for discussion, and asking thought-provoking Islamic questions. (3) motivating students: Encouraging students to develop enthusiasm and to aspire Islamic preachers on the international stage. (4) connecting to previous material: Relating previously studied topics such as the language features and schematic structure for writing procedure texts. (5) incorporating religious knowledge: Relating the content to Islamic Education and Ethics, such as explaining how to perform prayer, or presenting Qur’anic verses and hadiths about ablution and Allah’s process of creating humans. (6) relating to daily life: Connecting the lesson to social daily life with Islamic multimodal product of procedure text.